DYNAMIC TENDENCIES OF THE STATE OF WOLF AND FOX POPULATIONS AND RABIES CASES ON THE TERRITORY OF POLTAVA AND SUMY REGIONS OF UKRAINE - Avramenko, N. O.; Omelchenko, G. O.; Petrenko, M. O. (Scientific Progress & Innovations, 2020)
Hunting resources need regular registration of their quantitative composition, studies of qualitative state of wild animals and their conditions of existence, as well as the search for effective solutions to eliminate hunting problems. The purpose of our research was to determine the correlation between the number of predatory animal populations and the number of rabies cases in Poltava and Sumy regions of Ukraine. The object of study was the number of productive predatory animals in Poltava and Sumy regions. The following species of carnivorous mammals of Canidae genus were selected: the wolf (Canis lupus L., 1758) and the fox (Vulpes vulpes L., 1758). Comparative analysis was the research method. To analyze the dynamics of the abundance of the common fox, we used the data of the State Statistics Committee, forms 2TP (hunting), the Statistical bulletin “On hunting management”, form 2TP (hunting), which were made during 2011–2019 by the State Statistics Service of Ukraine. According to the State Statistics Committee of Ukraine in the period 1978–2019, the largest number of foxes in Ukraine was observed in 1999 and 2000 (126,900 and 116,650 heads, respectively). Between 2000 and 2014, there was a sharp decrease in the fox population by more than 50 %, which, in our opinion, was the result of illegal hunting. Analyzing the dynamics of fox number in Pol-tava region for the period of 2011–2019, we came to the conclusion that during these years there were no sharp fluctuations in indicators, but in comparison with 2011–2013, during the above mentioned observation periods the number of foxes tended to increase. The analysis of fox number in Sumy region for the same pe-riod showed the opposite dynamics of reducing the number of animals by half from 2,651 heads in 2011 to 1,500 heads in 2019. The next stage of our research was to analyze the reporting of the State Statistics Committee of Ukraine as to wolf population in Ukraine as a whole, and in Poltava and Sumy regions. The number of wolves in Ukraine doubled from 1,190 in 1978 to 2,468 in 2013. During the following six years, no sharp fluctuations in the animal population occurred, and the average was 2,225±100.30. At the begin-ning of the analysis period (2011–2019), the number of wolves in Poltava region ranged from 17 in 2011 to 20 in 2012. In the next seven–year period (2013–2019), the number of animals averaged 6±1.07, and in 2019 the animals were not registered at all, which indicates the destruction of the wolf as a species in Poltava re-gion and may have catastrophic consequences. Not less serious situation developed in Sumy region during the same observation period. Thus, according to the State Statistics Committee of Ukraine during the period of 2011–2015 the number of animals averaged 75±6.60 heads, whereas in the following period (2016–2019), the average number of animals was 2±2.89 heads, which was by 97 % less than the primary indicators. The correlation analysis has revealed that with a decrease in the population of predatory animals, there is a tendency for increasing rabies cases, both in Poltava and Sumy regions of Ukraine. It has been established that during the periods of 2010–2019 there were significant fluctuations of such cases on the territory of Poltava region every 2–3 years. In the structure of animal rabies morbidity among foxes in Poltava region, there was a tendency to decreasing the number of cases during the period of 2015–2019. The opposite situation of rabies cases was observed among foxes in Sumy region: significant fluctuations were registered in 2010 and 2018. During 2015–2019, the tendency to increasing rabies cases was observed in Sumy region.